INDIVIDUALISME, KEMAUAN MENGAMBIL RESIKO, KREATIFITAS DAN KINERJA KARYAWAN PADA PERUSAHAAN DAERAH AIR MINUM (PDAM) KABUPATEN MERAUKE - Leonora Puspa; Simon Siamsa (EKONOMI & SOSIAL, 2019)
The purpose of this study is to analyze whether individualism and high willingness to take risks significantly influence the performance of each workforce and whether creativity mediates between individualism and high willingness to take risks on the performance of all workers. The place of this research is located in the Regional Water Supply Company (PDAM) of Merauke Regency, Papua Province. The population and sample of this research are the total workforce of 99 people. The method of data collection uses the questionnaire method (questionnaire) which uses a list of questions directly from the respondent. Data analysis techniques in this study used SEM analysis through the operation of the AMOS program. The results of the study explained that 1) Individualime influences performance, 2) Willingness to take risks influences performance, 3) Creativity influences performance, 4) Individualime influences performance through creativity as mediation, 5) Willingness to take risks influences workforce performance through creativity as mediation in the Regional Water Company (PDAM) of the Merauke Regency, Papua Province.